Causal Factors Affecting Competitive Advantages of Tourism in Jiangxi Province the People’s Republic of China - Fang, Luo; Teerapornlertratt, Preyaporn; Chantanasiri, Supattra; Kositkanin, Thananwarin (International Journal of Multidisciplinary in Management and Tourism, 2024)
This article aimed to study (1) the problem of tourism, (2) causal factors affecting competitive advantage of tourism and (3) propose and suggest tourism in Jiangxi Province the People’s Republic of China. Qualitative research, the sample group was 8 managers of tourism enterprises by purposive selection. Quantitative research, the sample group was 400 employees of tourism enterprises by simple random. The instrument for collecting data ware in-depth interviews and questionnaires. The data analysis used descriptive statistical analysis and Structural Equation Modeling. The research results were found as follows; 1. Jiangxi tourist attractions have the following problems: in terms of tourist attraction, the infrastructure needs to be improved, and some red tourism resources are short of experiential tourism and other highly participatory tourism models. In terms of tourism marketing and promotion strategies, the level of marketing personnel of some tourism enterprises such as souvenir shops needs to be improved, and the new media marketing methods of some well-known scenic spots need to be strengthened. In terms of government policy, the government needs to strengthen the restoration of cultural heritage and strengthen the integration of the cultural tourism industry. 2. Factors that affect the competitive advantage of Jiangxi’s tourism industry include tourism potential, tourism marketing and promotion strategies, and government policies. 3. Suggestions on improving the competitive advantage of tourism in Jiangxi Province People’s Republic of China. It is found that it is necessary to strengthen the experience of red tourism and enhance the attractiveness of tourism; introduce cutting-edge technology and upgrade infrastructure services; develop smart tourism and establish and improve smart marketing and marketing Mechanism; strengthen the construction of tourism talent team, comprehensively improve the service quality of tourism; introduce social funds to promote the restoration of cultural heritage; improve the cultural integration mechanism, give full play to the leading role of the government.